A Decade of Advances of CS2/Amines in Three-Component Reactions - Wang, Zhan-Yong; Li, Jiarong; Wang, Nan; Liu, Hong; Ding, Wanli; Wang, Kai-Kai (Synthesis, 2023)
Carbon disulfide (CS2) and amines are widely used in three-component reactions; commonly, dithiocarbamic acids are generated. As intermediates, dithiocarbamic acids are able to react with electrophiles, or nucleophiles. The goal of this review is to present an overview of CS2/amines in organic synthesis in the period 2011–2022. It focuses on reactions with alkenes, alkynes, I2, arynes, allenes, quinones, vinyl chlorides, aryl halides, arylboronic acids, 2-iodoanilines, 2-aminophenols, hypervalent iodine reagents, epoxide, or maleic anhydride.1 Introduction2 Reactions with Electrophiles3 As Radical Precursor4 Reactions with Nucleophiles5 Conclusions
Keywords: carbon disulfide; CS2; amine; three-component reaction; mechanism